2019
DOI: 10.1002/cbf.3376
|View full text |Cite
|
Sign up to set email alerts
|

Lin28a expression protects against streptozotocin‐induced β‐cell destruction and prevents diabetes in mice

Abstract: Lin28, which is highly expressed during embryogenesis, has been shown to play an important role in cell growth and embryonic development. Meanwhile, Lin28 represses let-7 miRNA biogenesis and block pre-let-7 processing in the cytoplasm.The let-7 family of miRNAs is known to repress oncogenesis and cell cycle progression by targeting oncogenic genes and signalling pathways. Consequently, Lin28 acts as an oncogene by upregulating let-7 targets through the repression of let-7 biogenesis. A recent genome-wide asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
(96 reference statements)
0
13
0
2
Order By: Relevance
“…We suggest that it is possible that the upregulation of Let-7 in the hippocampus could aggravate the toxic effects of STZ via further dysregulation and inhibition of the insulin signaling pathway. This suggestion can be supported by a recent study that found that LIN-28a, which is a powerful inhibitor of Let-7 biogenesis, prevented the toxic effects of STZ on pancreatic β-cells, and that LIN-28a downregulation of Let-7 was associated with increased phosphorylation of PI3K and Akt in a mouse insulinoma cell line (Sung et al, 2019). Interestingly, estrogen binding to G-coupled estrogen receptor (GPER) could result in the activation of the PI3K/Akt pathway (Peixoto et al, 2017;Bian et al, 2019), which could lead to memory enhancement (Frick, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…We suggest that it is possible that the upregulation of Let-7 in the hippocampus could aggravate the toxic effects of STZ via further dysregulation and inhibition of the insulin signaling pathway. This suggestion can be supported by a recent study that found that LIN-28a, which is a powerful inhibitor of Let-7 biogenesis, prevented the toxic effects of STZ on pancreatic β-cells, and that LIN-28a downregulation of Let-7 was associated with increased phosphorylation of PI3K and Akt in a mouse insulinoma cell line (Sung et al, 2019). Interestingly, estrogen binding to G-coupled estrogen receptor (GPER) could result in the activation of the PI3K/Akt pathway (Peixoto et al, 2017;Bian et al, 2019), which could lead to memory enhancement (Frick, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have shown that constitutively active Akt inhibits fatty acid-stimulated apoptosis in β-cells ( 27 , 28 ), and β-cell specific overexpression of Akt has also been shown to prolong cell survival and protect against streptozotocin-induced diabetes ( 29 ). In several cells, pancreatic β-cells, muscle cell and cardiomyocytes Lin28a has been reported to prevent apoptosis and regulate the PI3K/Akt/mTOR pathway through downregulation of micro RNA Let-7 ( 15 , 30 , 31 ). We found that INS-1 cells treated with high glucose had decreased phosphorylation of Akt and mTOR while Lin28a overexpression recovered the high glucose-induced downregulation of p-Akt and p-mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the blood glucose level is attributed to the cytotoxic effect of STZ on pancreatic cells (Waly et al, 2015). In addition, STZ leads to destruction of β-cells of Islets of Langerhans and malfunctioning of the pancreas resulting in the blood glucose elevation (Sung et al, 2019;Agila and Kavitha, 2012).…”
Section: Discussionmentioning
confidence: 99%